Pharmacological and non-pharmacological pain relief for office hysteroscopy: an up-to-date review. (3rd July 2020) - Riemma, G.; Schiattarella, A.; Colacurci, N.; Vitale, S. G.; Cianci, S.; Cianci, A.; De Franciscis, P.
Abstract: In-office hysteroscopy is considered the standard technique for visualization of the uterine cavity and the diagnosis of intrauterine pathologies. Moreover, nowadays, it is possible to treat a vast number of intracavitary diseases in the office, without the need for the inpatient setting. However, in some cases, pain might occur, and this is the most common reason for not completing the procedure. Over the last 20 years, many efforts have been carried out to miniaturize the instrumentation and to improve the techniques in order to avoid discomfort. Nonetheless, hysteroscopy still provokes distress for many patients. For this reason, pharmacological and non-pharmacological treatments for intraoperative and postoperative pain relief have been widely used for in-office hysteroscopy, with different results in various groups of women. The purpose of this review was to analyze the current literature on pharmacological aids (non-steroidal anti inflammatory drugs, cyclooxygenase-2 inhibitors, antispasmodics, local anesthetics, prostaglandins, opioids) and non-pharmacological interventions (transcutaneous electrical nerve stimulation, uterine stretching, uterine pressure, warming of distension medium, hypnosis, music, vocal–local) and to evaluate their impact on the relief from pain experienced during in-office hysteroscopy.